Implementation of credit risk management in an effort to minimize the level of non-performing loans (npl) at bank banten for the 2020-2024 period - Nur Izati, Siti Salma; Lesmana, Ihwan Satria; Anwar, Khaerul (Institute of Computer Science (IOCS), 2025)
This study aims to evaluate the implementation of credit risk management at Bank Banten in reducing the Non-Performing Loan (NPL) ratio from 2020 to 2024. In the banking sector, NPL is a key indicator that reflects the quality of the credit portfolio as well as the effectiveness of the bank’s risk management. Bank Indonesia has set a reasonable threshold for NPL at below 5%. If this figure is exceeded, it may indicate deficiencies in the bank's credit risk management. This research uses a descriptive qualitative approach, with data collected through in-depth interviews, observations, document analysis, and Focus Group Discussions (FGD). The key informants in this study included the credit risk manager, credit officers, and analysts from Bank Banten. The results of the study show that Bank Banten experienced a significant decrease in the gross NPL ratio, from 22.27% in 2020 to 7.53% in 2024. This decline is attributed to the restructuring of credit policies, improvement of the risk monitoring system, and the stricter application of prudent credit principles. In addition, an Early Warning System (EWS)-based technology was introduced in 2023. The credit risk mitigation strategies implemented included enhanced credit analysis, more thorough assessments of debtor feasibility, and tighter supervision of problematic loans. Bank Banten also involved internal stakeholders in the formulation of risk strategies to ensure effectiveness and compliance with Financial Services Authority (OJK) regulations. The conclusion of this study is that the implementation of credit risk management at Bank Banten during the research period has been effective in reducing the NPL ratio, although there is still room for improvement in debtor financial literacy and strengthening the risk management information system. These findings are expected to serve as a reference for other regional development banks to improve credit management quality and maintain financial stability.